You, the Leader (HBR Women at Work Series) - Review, Harvard Business. (HBR women at work series., 2022)
It's time for female leaders to stand out. Women often aren't seen for their leadership potential. We face a double bind, forced to choose whether to be liked or respected, while neither one alone is enough to secure a seat at the table. It's up to organizations to change, but until then, what's an aspiring female leader to do? You, the Leader tackles the obstacles you face as you chart your path to the top, from not getting credit for your work to feeling unseen to being subjected to unfair biases and expectations. Filled with advice, tips, and relatable conversations, this book will help you better understand how you can remain authentic while showing yourself as a valued leader in your organization. This book will inspire you to: See yourself as a leader Develop an executive voice Advocate for yourself and your work Support the women around you The HBR Women at Work series spotlights the real challenges and opportunities women experience throughout their careers. With interviews from the popular podcast of the same name and related articles, stories, and research, these books provide inspiration and advice for taking on topics at work like inequity, advancement, and building community. Featuring detailed discussion guides, this series will help you spark important conversations about where we're at and how to move forward.